Soil physical health under different farming systems of rice fields and its effect on rice (Oryza sativa L.) productivity - Ganjar Herdiansyah; Mujiyo Mujiyo; Aktavia Herawati; Hanindyo Bramastomo (Наукові горизонти, 2024)
Soil physical health was affected by several factors including farming systems, and the plant growth and soil productivity were directly affected. The study of soil physical health in different farming systems will help manage soil and water used processes. The purpose of this study was to determine the effect of the paddy field management system on soil physical health status, to identify determinants of soil physical health status, and to formulate appropriate management solutions to improve soil physical health. This study employed descriptive, explorative, and survey approaches with purposive sampling methods in soil sampling. The findings showed that the physical health status of soil on paddy fields in the Tirtomoyo District was classified into moderately healthy and healthy categories. Differences in the management system of paddy fields affect soil physical health. Organically managed rice fields have the highest soil physical health value of 76.69. Semi-organic and inorganically managed paddy fields have lower health values of 71.48 and 69.11, respectively. Soil penetration resistance, soil porosity, and soil texture are determining factors because they can improve indicator conditions and soil physical health values. Efforts can be made to improve soil physical health status by applying organic fertilisers and biochar to paddy fields. Having established the relationship between soil physical health values and rice yield productivity, it is anticipated that farmers and stakeholders will be able to increase crop productivity through improving soil physical condition